2013
DOI: 10.1371/journal.pone.0058763
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for the Discovery of Essential Proteins

Abstract: BackgroundExperimental methods for the identification of essential proteins are always costly, time-consuming, and laborious. It is a challenging task to find protein essentiality only through experiments. With the development of high throughput technologies, a vast amount of protein-protein interactions are available, which enable the identification of essential proteins from the network level. Many computational methods for such task have been proposed based on the topological properties of protein-protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
80
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 40 publications
0
80
0
Order By: Relevance
“…The protein-protein interactions (PPI) form a complex network represented as a graph, where the nodes represent proteins and undirected edges connecting these nodes represent the interactions between the proteins [32, 33]. Generally, PPI networks have shown to be a great vehicle for developing new hypotheses and designing novel laboratory experiments [34, 35]. Furthermore, essential proteins can be identified by topological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The protein-protein interactions (PPI) form a complex network represented as a graph, where the nodes represent proteins and undirected edges connecting these nodes represent the interactions between the proteins [32, 33]. Generally, PPI networks have shown to be a great vehicle for developing new hypotheses and designing novel laboratory experiments [34, 35]. Furthermore, essential proteins can be identified by topological analysis.…”
Section: Introductionmentioning
confidence: 99%
“…SC counts the total number of closed walks in which a protein participates in the PIN and gives more weights to closed walks of short lengths [21]. It has been confirmed that these topological properties correlate with the essentiality of proteins to some degree [12, 18, 22, 23]. Some recently proposed methods are also based on the topological properties of PINs, such as TP [24] and LAC [25], and they outperform the mentioned commonly used centrality measures.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Computationally analyzed PPIs help in developing new hypotheses about an organism and designing the laboratory experiments driven by the hypotheses. 10,11 In the case of infectious microorganisms, studying PPI networks offers identification of pathogenic proteins and therefore offers new opportunities for developing novel drugs and vaccines. [12][13][14] The interactions of proteins within a cell depend on several biological or physicochemical factors 15 and the PPI can be physical interactions, regulatory associations, genetic interactions, structural interactions, functional similarity associations among others.…”
Section: Introductionmentioning
confidence: 99%